Study on failure charactersitcs and life prediction method of IGBT in traction converter - Liu, Haitao; Liu, Xingping; Kang, Lixuan; Liu, Wenye; Xiang, Chaoqun (Dianji yu Kongzhi Xuebao = Electric Machines and Control, 2025)
The IGBT is the most critical component in the traction system while also exhibiting a high failure rate. The way to utilize operational condition data from traction converters to extract IGBT working characteristics constitutes a key challenge. To enhance the reliability of traction converters during operation, an IGBT service life prediction method specifically was proposed for locomotive traction converters. Through analyzing IGBT module samples collected from several years of field operation, failure modes were identified. Accelerated lifespan testing at the converter component level under simulated field conditions was conducted, establishing an IGBT lifespan model. Subsequently, an online loss and junction temperature calculation model for traction converters was developed. By real-time acquisition of operational parameters and electrical data during line operation, this model continuously computes IGBT power losses and junction temperatures. Online rainflow counting was employed to statistically analyze thermal stresses, enabling lifespan model-based prediction of IGBT remaining service life. Finally, an IGBT lifespan prediction device for traction converters was implemented and validated through practical application on operational railway lines. The proposed method demonstrates streamlined computation processes, high efficiency, and significant engineering application value.